2017
DOI: 10.1161/hypertensionaha.116.08395
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Interferon Regulatory Factor 3 Protects Against Atherosclerosis in Apolipoprotein E–Deficient Mice

Abstract: The secretion of adhesion molecules by endothelial cells, as well as the subsequent infiltration of macrophages, determines the initiation and progression of atherosclerosis. Accumulating evidence suggests that IRF3 (interferon regulatory factor 3) is required for the induction of proinflammatory cytokines and for endothelial cell proliferation. However, the effect and underlying mechanism of IRF3 on atherogenesis remain unknown. Our results demonstrated a moderate-to-strong immunoreactivity effect associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 45 publications
0
33
0
1
Order By: Relevance
“…Utilizing chromatin immunoprecipitation (Chip) assay in HUVECs, followed by PCR of ICAM-1 and VCAM-1 promoters, a specific and direct binding of IRF3 to region P1 of ICAM promoter was confirmed. 5 Depletion of IRF3 using specific siRNA in HUVECs and subsequent treatment with TNF-α, correlated with significant decrease in ICAM-1 and VCAM-1 expression at both the mRNA and protein levels. 5 Together, these findings highlight an established network of inflammatory trigger on endothelial integrity, and subsequent pro-atherogenic events via altered secretion of adhesion molecules.…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…Utilizing chromatin immunoprecipitation (Chip) assay in HUVECs, followed by PCR of ICAM-1 and VCAM-1 promoters, a specific and direct binding of IRF3 to region P1 of ICAM promoter was confirmed. 5 Depletion of IRF3 using specific siRNA in HUVECs and subsequent treatment with TNF-α, correlated with significant decrease in ICAM-1 and VCAM-1 expression at both the mRNA and protein levels. 5 Together, these findings highlight an established network of inflammatory trigger on endothelial integrity, and subsequent pro-atherogenic events via altered secretion of adhesion molecules.…”
mentioning
confidence: 92%
“…In response to stimuli, IRF3 may become activated via phosphorylation, and translocate into the nucleus. 5 In this study, the authors observed that IRF3 was increased in patients with coronary heart disease (CHD). Upregulated IRF3 level was confirmed further using ApoE-deficient mice, a commonly used atherosclerotic mice model relative to IRF3 −/− ApoE −/− .…”
mentioning
confidence: 93%
See 3 more Smart Citations